Rede especial : uma proposta de inclusão digital e social em ações sócio-educativas - Rodrigues, Ana Cristina (2006)
The objective of this research is to make an interactive frame between educational computing and its contributions to disabled people. Important aspects about exclusion and social and digital inclusion, which are part of this research process, are discussed. The issue of social exclusion in important periods of history of humankind is also studied. In this context we will study the use of assistive technologies as pedagogical tools to help disabled students of the Computing Program in Special Education (Programa de Informática na Educação Especial, INFOESP) in the social institution Obras Sociais da Irmã Dulce (OSID). We also tell the story of Sister Dulce's life and the beginning of her work in the city of Salvador, Bahia. This was the starting point of the INFOESP. The methodology used is a case study focusing on the INFOESP program of the Center of Rehabilitation and Prevention of Disabilities (Centro de Reabilitação e Prevenção de Deficiências, CRPD) of Obras Sociais da Irmã Dulce.